STRATEGI DAN PERAN GURU PAI DALAM MEMBENTUK KARAKTER IBADAH (SHALAT DAN PUASA) SISWA DI SMP ISLAM TERPADU INSAN QUR’ANI PONCOWARNO - ZAMRONI, MUHAMMAD (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
This study aims to analyze the strategies and roles of Islamic Religious Education (PAI) teachers in shaping the character of prayer (salat) and fasting (puasa) among students at SMP Islam Terpadu Insan Qur’ani Poncowarno. This research employs a qualitative approach with anethnographic method. The research subjects were selected using purposive sampling, with the PAI teacher as the primary informant, while students and school documents served as supporting informants. Data collection techniques included participatory observation, in-depth interviews, and documentation. Data analysis followed the Miles, Huberman, and Saldaña model, which involves data condensation, data display, and conclusion drawing. The findings reveal that PAI teachers implement three main strategies in shaping students’ worship character. First, the habituation strategy through the regular implementation of midday congregational prayers every day. Second, the role-modeling strategy demonstrated by teachers through their daily religious behavior. Third, the guided worship practice strategy that provides students with direct learning experiences. Additionally, the school supports these efforts through various religious programs, including regular religious guidance, Ramadan pesantren kilat (intensive Islamic boarding school program), and worship monitoring through daily worship logbooks. In this process, PAI teachers simultaneously act as educators, mentors, motivators, and role models. This study concludes that the formation of worship character isnot solely derived from formal programs but is shaped through a living religious culture embedded in the daily interactions between teachers and students. The transformation from external compliance to internal awareness serves as an indicator of successful character education. This study recommends that future researchers conduct comparative studies across educational institutions, employ quantitative or mixed-method approaches, and expand the focus to include other stakeholders such as parents and school principals.